A pena de perdimento no Direito Aduaneiro brasileiro - Bruyn Júnior, Herbert Cornelio Pieter de (2016)
This thesis intends to demonstrate the constitutionality of the forfeiture penalty in the Brazilian Customs Law through a syntactic, semantic and pragmatic analysis of the rule. It examines, therefore, the concept of sanctions, the foreign trade context, the meaning of this penalty in the current legislation and the way the administrative bodies and case law have applied these rules